FAMILY FIRMS: COVID-19 CHALLENGES AND FUTURE OUTLOOK - Banerjee, Anandi (International Journal of Accounting & Finance Review, 2021)
The COVID-19 pandemic endangered the survival of many firms and emphasized the need to reevaluate corporate strategy. This paper studies the impact of the pandemic on family businesses and how it changed their strategy, priorities, and outlook. We use data from the PricewaterhouseCoopers (PwC) Family Business Survey 2021 that covers 2,801 family firms in 87 countries. Our study highlights some of the challenges family businesses faced during the pandemic and the need for an updated blueprint to ensure their long-lasting success. The survey draws attention to the financial resilience of family businesses and their unique advantages in terms of reputation and trust. However, it also underscores the need for family firms to adopt a more focused environment, social and governance (ESG) agenda, and to invest in technological transformation. The paper analyzes the congruity between academic research and CEO responses and forms a bridge between the academic literature on family firms and the real-world surveys of CEOs of family businesses conducted by PwC.JEL Classification Codes: G32, M10, M53, L20, L21.